Hubungan Indeks Massa Tubuh (IMT) Dengan Derajat Dismenore Pada Mahasiswi Fakultas Kedokteran Universitas Muhammadiyah Makassar Angkatan 2021 - Raniyati, Wa Ode; Irwan, Andi Alamsyah; Mali, Rusli (Indonesian Journal of Health, 2023)
Dysmenorrhea is pain during menstruation, and most women experience some degree of pain at least on the first day of menstruation. The effects of dysmenorrhea cause 13% to 51% of women to be absent at least once on a work day and 5% to 14% to be absent from work due to severe symptoms of dysmenorrhea. To find out the relationship between body mass index (BMI) and the degree of dysmenorrhea in medical students, this study used an observational analytic method through a cross-sectional study approach. A total of 113 samples were taken using the sampling method from the inclusion criteria, namely the criteria for active female students at the Faculty of Medicine, University of Muhammadiyah Makassar class of 2021 and having a history of pain during menstruation in the last six months and exclusion criteria, namely students who have other diseases with symptoms of abdominal pain or pelvic pain, for example peritonitis. , Urinary Tract Infections, Appendicitis, and others, female students who have previous illnesses (endometriosis, adenomyosis), female students who have a history of taking anti-depressant drugs and female students who have mental disorders or stress. The analysis used is Univariate analysis and Bivariate analysis. The results of this study showed that there were 73 (64.6%) respondents with good BMI while 40 (35.4%) respondents had bad BMI. There were 69 (61.1%) respondents who had mild degrees of dysmenorrhea, 34 (30.1%) of respondents had moderate degrees of dysmenorrhea and 10 (8.8%) of respondents had severe degrees of dysmenorrhea. So based on the results of the above study it can be concluded that most respondents have good BMI and some have mild dysmenorrhea and from the results of bivariate data analysis between BMI and the degree of dysmenorrhea, there is no correlation between BMI and the degree of dysmenorrhea and the p value is 0.462 or more than 0.05.